Beyond Personal Factor: A Multilevel Analysis for Predicting the Effect of Moral Self-regulation and School Climate on Muslim Adolescent Aggressivity - Zahrotun Nihayah; Wara Alfa Syukrilla; IM Hambali; Mohamad Fayruz (Islamic Guidance and Counseling Journal)
Aggressive behaviors among adolescents have been increasingly observed in Indonesian Islamic boarding schools (pesantren), garnering significant attention due to their incongruity with the schools' ethos. Addressing these behaviors in pesantren requires a different approach from mainstream schools due to their unique characteristics. This study investigates the impact of moral self-regulation and school climate on aggressiveness among Muslim adolescents, using a multilevel analysis that considers both individual and institutional factors within the educational setting as units of analysis. This quantitative study involved 428 participants (mean=16.45, SD=1.01) both males and females from ten pesantren in three provinces in Indonesia selected using convenience sampling. Data were collected using the modified version of the aggressivity scale, moral self-regulation scale, and school climate scale. They were analyzed using multilevel regression analysis techniques with the aid of the R lmerTest program. An initial evaluation of the need for multilevel analysis was done by checking the significance of the Likelihood Ratio Test (LRT) results for the Intercept models and Intraclass correlation (ICC) above 5%. LRT and Akaike Information Criterion (AIC) were used as the selection criteria for the best hierarchical models involving random intercepts and random slopes. The study found that better moral self-regulation in students significantly reduces adolescent aggressivity. Additionally, a positive school climate helps prevent aggressive behavior among students. Addressing aggression in Muslim adolescents in Indonesia requires focusing on both individual and school factors that promote positive behavior, emphasizing the importance of moral self-regulation and a supportive school environment.